Student knowledge and awareness of oral cancer (study at Senior High School 2 Baubau, Southeast of Sulawesi) - Anna Mardhiana; Harlina Harlina (Journal of Dentomaxillofacial Science, 2016)
Oral cancer is a malignancy which came from oral mucosal epithelial and other oral’s part including from saliva glands (majority the minor one) inside the mouth. Oral cancer has a quick spread. A half of oral cancer diagnosed at a late stage with a high level of death. Only half of this malignancy sufferer survive more than five years. However, the survival prognosis will increase 80-90% if the cancer could diagnose in early stage. The objective of this study is to measure qualitatively oral cancer knowledge and awareness among the students at SMAN 2 Baubau. This study is descriptive study by cross-section approach. Oral cancer knowledge and awareness among the students in SMAN 2 Baubau is in a low stage. Students hardly hear the information about the signs of oral cancer and have no idea what must they do if they find someone presented with one of the oral cancer signs. The reason behind unknown action lack of information and socialization about oral cancer.